Peran Komunikasi Sebagai Upaya Membangun Perilaku Kewirausahaan Petani Mangga di Kabupaten Majalengka - Rani Andriani Budi Kusumo; Elly Rasmikayati; Gema Wibawa Mukti (Paspalum: Jurnal Ilmiah Pertanian, 2018)
Market demand, especially structured markets demands quality and continuity of production, in addition to the quantity aspect. Mango farmers in Majalengka Regency have also not been fully able to meet market demand, especially in terms of quality and product continuity. Farmers must be able to follow market demand in order to survive in their business and be able to compete with mango farmers in other countries. The limitations of farmers in accessing capital, markets and information often become obstacles for farmers in developing their businesses. The purpose of this study was to analyze the accessibility of farmers to agricultural information and analyze the relationship of farmers' accessibility to agricultural information with entrepreneurial behavior of mango farmers in Majalengka District. Entrepreneurial behavior of farmers can be built one of them through appropriate communication strategies so that mango farmers can develop their businesses to improve the welfare of farmers. The research was carried out with Survey-explanatory method. Farmers were taken randomly as many as 100 people. Data analysis was carried out descriptively and inferently. To analyze the relationship between various variables the research was carried out by rank Spearman correlation analysis. The results of this study showed that some farmers find it quite difficult to obtain information about technical cultivation and climatic or weather conditions, while market information is perceived to be easily accessible to most farmers. Entrepreneurial behavior is related to farmers' accessibility to cultivation information and climatic or weather conditions. Information and communication technology can be used to improve farmers' accessibility to agricultural information